Accuracy of ultrawide-field fundus ophthalmoscopy-assisted deep learning for detecting treatment-naïve proliferative diabetic retinopathy - Toshihiko Nagasawa; Hitoshi Tabuchi; Hiroki Masumoto; Hiroki Enno; Masanori Niki; Zaigen Ohara; Yuki Yoshizumi; Hideharu Ohsugi; Yoshinori Mitamura (2019)
We investigated using ultrawide-field fundus images with a deep convolutional neural network (DCNN), which is a machine learning technology, to detect treatment-naïve proliferative diabetic retinopathy (PDR).We conducted training with the DCNN using 378 photographic images (132 PDR and 246 non-PDR) and constructed a deep learning model. The area under the curve (AUC), sensitivity, and specificity were examined.The constructed deep learning model demonstrated a high sensitivity of 94.7% and a high specificity of 97.2%, with an AUC of 0.969.Our findings suggested that PDR could be diagnosed using wide-angle camera images and deep learning.